Pengelolaan Penilaian Sikap Sosial dalam Pembelajaran Muatan Lokal Bahasa Jawa di Kelas II SDN Bayan No 216 Surakarta - Windarisni, Ruvina; Prof. Dr. Sutama, M. Pd, Prof. Dr. Sutama, M. Pd; Dr. Wafrotur Rohmah, MM, Dr. Wafrotur Rohmah, MM (2016)
Therefore in this study discusses how social attitudes in the management of local content lessons Java language . The purpose of this study is to describe the management of Assessment attitude of Social in Education Local Content Java language in second grade of SDN Bayan No. 216 Surakartadid by Master , to describe the management of Assessment attitude of Social undertaken in Learning Local Content Java language in class II SDN Bayan No. 216 by students in. This research is using qualitative descriptive case study design . This research was done in second grade of SDN Bayan No. 216 Surakarta . The study was done from September 2015 - March 2016. The data in this study are primary data are using words , observation data , secondary data is the document . Data Source using the words , documents . The resource person were the Principal , Teacher 2 A , Teacher 2B and Headmaster. The technique of collecting data through observation , interviews and documentation study . Mechanical analysis is using interactive analysis . The validity of the data are using a triangulation of sources and methods . The results of the research management of social attitudes carried out by teachers include observation and journals . Its implementation includes planning , implementation and evaluation . Management assessment of social attitudes was done by students include self assessment and peer assessment . The simply implementation is done orally and still guided by teachers. Conclusion The management of social attitudes assessment carried out by teachers include observations and Journal . Attitude assessment done by teachers has been going well and implemented properly . Management assessment of social attitudes conducted by students include self-assessment and peer assessment . Assessment by the students has not gone well